Study on powder particle behavior in powder spreading with discrete element method and its critical implications for binder jetting additive manufacturing processes. Issue 1 (31st December 2023) - Wu, Shibiao; Yang, Yongqiang; Huang, Yanlu; Han, Changjun; Chen, Jie; Xiao, Yunmian; Li, Yang; Wang, Di
ABSTRACT: Understanding powder bed system behaviour in powder spreading is a fundamental issue in binder jetting additive manufacturing (BJAM). This work established a discrete element model incorporating a parallel bond model to compatibly depict local cross-links between powder particles. BJAM parameters including layer thickness, gap compensation, recoat speed, rotation speed, and layer number were studied quantitatively for their effects on recoated powder's packing density and microscopic pore size and bonded layer's breakage and layer shift. Evolutions and influence mechanisms on both layer shift and bond breakage were further elucidated. Some practical implications include: gap compensation corresponding to an ideal recoated powder structure is ∼75 μm; rotation speed should be controlled at 40–120 rad/s to avoid low-rotation-speed layer shift surge and high-rotation-speed breakage; layer shift occurring at a certain stage is irreversible and must deserve well-maintained. This research can provide theoretical guidance for developing BJAM and even support-free powder bed – based additive manufacturing.